Dysregulated lipid metabolism in kidney stone pathogenesis: a literature review of mechanistic insights and therapeutic implications - Quan Wen; Qiuyu Li; Haoji Zhou; Boyan Su; Yalin Ren; Qiqi He (BMC Urology)
Abstract Kidney stone disease (KSD) is a globally prevalent urinary system disorder whose pathogenesis involves complex interactions among metabolic, genetic, and environmental factors. Although the role of glucose metabolism in KSD has been widely studied, the impact of lipid metabolism abnormalities remains unclear. This review systematically integrates epidemiological, animal model, and molecular mechanism studies to explore the mechanisms by which lipid metabolism disorders promote KSD through key regulatory factors, such as peroxisome proliferator-activated receptors (PPARs), fatty acid-binding proteins (FABPs), and apolipoproteins, synergizing with organelle damage pathways, including mitochondrial dysfunction, endoplasmic reticulum stress (ERS), and ferroptosis. This study revealed that abnormal lipid metabolism accelerates renal papillary calcification and stone formation by inducing oxidative stress, inflammatory cascade reactions, and crystal adhesion. Additionally, small-molecule modulators targeting the PPAR/FABP pathway and novel delivery systems, such as mitochondrion-targeted liposomes, have demonstrated the potential to intervene in the lipid metabolism/organelle damage axis, although clinical translation faces challenges such as species differences (The paradoxical effects of PPARα agonists in rodents versus humans) and safety concerns. This review highlights the importance of lipid metabolism as a new target for KSD prevention and treatment, and it suggests that future research should focus on the analysis of molecular mechanisms and the clinical translation of interdisciplinary technologies (e.g., mitochondrion-targeted delivery systems). Graphical Abstract